Honey from Tiúba stingless bees (Melipona fasciculata) produced in different ecosystems: physical and sensory studies - Fernandes, Rachel Torquato; Rosa, Ivone Garros; Conti-Silva, Ana Carolina [UNESP] (Wiley, 2020)
BACKGROUND: Honey from Tiúba stingless bees (Melipona fasciculata) produced in three different ecosystems in Brazil (Cerrado, Litoral and Baixada), as well as a sample of honey from Apis mellifera bees from the Baixada region for comparison, were evaluated regarding viscosity, color, sensory profile and sensory acceptance. RESULTS: The honey from Tiúba was less viscous, with a darker color and lower purity of the color (chroma) in relation to honey from Apis mellifera. The sensory profile firmly differentiates the honeys. The Apis honey was mainly described as opaque, viscous and adhesive. Tiúba honey from the Cerrado region stood out as semi-bright, acid taste, alcoholic, propolis, bitter taste and spicy. Tiúba honey from the Litoral region was characterized by its yellow color, woody odor and medicine flavor. The Tiúba honey from the Baixada region was described as gold colored, fluid and citric. The Tiúba honey from the Cerrado region had similar sensory acceptance to the Apis honey, probably because it was specifically characterized through attributes of odor and flavor. On the contrary, the Tiúba honey from the Litoral and from the Baixada regions was less well accepted. CONCLUSION: The honeys are different regarding their physical and sensory properties, differences that result from the bee species and from the geographical origin of the honey. This study could contribute to the creation of a standard identity and specific quality for Melipona fasciculata honey, also contributing to its production and commercialization not only in Brazil, but also internationally. © 2020 Society of Chemical Industry.
Keywords: CATA test; color; Maranhão; meliponines; sensory acceptance; viscosity